PRACTISE AND BENEFITS OF INDEX BENCHMARKING (Perner's Contacts, 2009)
This article deals with problems of index benchmarking and its usage aspects especially in small and medium enterprises. It emphasizes importance of this discipline for keeping or increasing of enterprise competitiveness and it is focused particularly on principle function of benchmarking process on the basis of benchmarking database of domestic and foreign enterprises.
Keywords: index benchmarking; comparison; benchmark index; Small and Medium Enterprises; finance; turnover; criteria; figure